Literature Review Filantropi Islam antara Tahun 2008 hingga 2018 - Aris Puji Purwatiningsih; Muchlis Yahya (AL-MUZARA'AH, 2018)
The author is interested in reviewing Islamic philanthropic literature between 2008 and 2018 because Islamic philanthropic behavior is found in any community, from the scope of the poorest countries to even the developed world. In addition, Islamic philanthropy is an object of study that has been widely studied in the social and economic fields. Articles about Islamic philanthropy were obtained using the zakat keyword on Emerald Insight between 2008 and 2018. The search results of 37 articles were then grouped into six topics discussing management, CSR, philanthropy, poverty, charity, religion, distribution, and collection. The findings show that Islamic philanthropy is a topic that is widely discussed by economists and researchers both muslim and non muslim. This is because Islamic philanthropy is the most realistic way to reduce poverty and social inequality today. However, the lack of optimal management of potential Islamic philanthropic funds has hampered the achievement of this goal.